2014
DOI: 10.1128/aem.03130-13
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ethanol Fermentation in Saccharomyces cerevisiae Sake Yeast by Disrupting Mitophagy Function

Abstract: c Saccharomyces cerevisiae sake yeast strain Kyokai no. 7 has one of the highest fermentation rates among brewery yeasts used worldwide; therefore, it is assumed that it is not possible to enhance its fermentation rate. However, in this study, we found that fermentation by sake yeast can be enhanced by inhibiting mitophagy. We observed mitophagy in wild-type sake yeast during the brewing of Ginjo sake, but not when the mitophagy gene (ATG32) was disrupted. During sake brewing, the maximum rate of CO 2 producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…In East and Southeast Asia, various cereals fermented by fungi are widely used as starchhydrolyzing catalysts for the production of rice-derived alcoholic beverages. These include Japanese sake (5,6) and shochu, Korean Makgeolli, and Chinese Huangjiu, as well as various other fermented foods such as soy sauce and miso (7). Koji is a mixture of steamed cereals cultured with nonpathogenic fungi, such as Aspergillus oryzae and Aspergillus luchuensis, including Aspergillus kawachii and Aspergillus awamori (the national fungi of Japan).…”
mentioning
confidence: 99%
“…In East and Southeast Asia, various cereals fermented by fungi are widely used as starchhydrolyzing catalysts for the production of rice-derived alcoholic beverages. These include Japanese sake (5,6) and shochu, Korean Makgeolli, and Chinese Huangjiu, as well as various other fermented foods such as soy sauce and miso (7). Koji is a mixture of steamed cereals cultured with nonpathogenic fungi, such as Aspergillus oryzae and Aspergillus luchuensis, including Aspergillus kawachii and Aspergillus awamori (the national fungi of Japan).…”
mentioning
confidence: 99%
“…Recently, several studies have focused that the mitochondrial activities have a role in the progression of the alcohol fermentation (31). For example, it was reported that the mitochondrial activity of yeast used for brewing Japanese sake affected malate and succinate production during alcoholic fermentation (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported as well by the decrease of malic acid in strains overexpressing malic enzyme, which catalyzes the conversion of malic acid to pyruvic acid in mitochondria (Redzepovic et al, 2003). In contrast, Kitagaki et al proposed a new pathway that involves manipulation of mitochondrial phenotypes such as morphology and activity to increase the rate of malic acid synthesis (Kitagaki & Shimoi, 2007;Kitagaki et al, 2008;Kitagaki, 2009;Motomura et al, 2012;Kitagaki & Takagi, 2013;Shiroma et al, 2014). Furthermore, Nakayama et al (2012) demonstrated that the high level of malic acid produced by the sake yeast strain No.…”
Section: Introductionmentioning
confidence: 99%
“…Because mitochondria are the site of oxidative respiration, their role in determining the fermentation profile during alcoholic fermentation has long been debated (Albertin et al ., ). However, we previously demonstrated that mitochondrial membrane potential affects fermentation profiles (Kitagaki & Shimoi, ; Kitagaki et al ., ; Kitagaki, ; Motomura et al ., ; Kitagaki & Takagi, ; Shiroma et al ., ). For example, mitochondrial morphology was first shown to affect the rate of malic acid synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation